Assessment of epigenotoxic profiles of Dongjiang River: A comprehensive of chemical analysis, in vitro bioassay and in silico approach. (1st August 2021) - Hu, Junjie; Liu, Jinhuan; Lv, Xiaomei; Yu, Lili; Lan, Shanhong; Li, Yanliang; Yang, Yan
Abstract: This research explored the occurrence, epigenetic toxic profiling and main toxic pollutants of POPs in surface water of Dongjiang River, southern China. The concentrations of selected POPs including polycyclic aromatic hydrocarbons (PAHs), endocrine disrupting chemicals (EDCs), phthalate esters (PAEs) and polybrominated diphenyl ethers (PBDEs) of surface water from 18 sites were investigated. ∑16 PAHs and ∑4 EDCs were at a moderate level, while ∑6 PAEs and ∑6 PBDEs had low pollution levels. PAHs, EDCs and PAEs showed higher concentrations in dry season than those in wet season, and the loading of selected POPs in tributaries was higher than those in mainstream due to intensive manufactures and lower runoff volume. Moreover, activities of DNA methyltransferase (DNMT)1, histone deacetylase (HDAC2, HDAC8) were confirmed to be sensitive indicators for epigenetic toxicity. The DNMT1-mediated epigenetic equivalency toxicity of organic extracts in Dongjiang River were more serious than those of HDAC2 and HDAC8. Correlation analysis shown binding affinity between POPs and DNMT1, HDAC2 and HDAC8 could be regarded as toxic equivalency factors. Risk assessment suggested that 4-nonylphenol and bisphenol A were the largest contributors to epigenetic risk. This study is the first attempt to quantify epigenetic toxicity and epigenetic risk evaluation of river water. Graphical abstract: Image 1 Highlights: A battery of in vitro bioassays were adopted for epigenetic toxicity test. Epigenetic toxic equivalency concentrations of water from Dongjiang river were determined. Binding affinity could be used as epigenetic toxic equivalency factor for risk assessment. Epigenetic risk of river water at DNMT1, HDAC2 and HDAC8 mediated pathway were assessed. BPA and 4-NP were the main contributors of epigenetic risk in Dongjiang river. Abstract : Binding affinity between POPs and epigenetic modulators was used as toxic equivalency factors for epigenetic risk assessment in Dongjiang River.